Estetika Timur Dalam Teater Tradisional Kemidi Rudat Lombok - F.M Marijo, M. Okta Dwi Sastra; Jazuli, M.; Mari’i, Mari’i (Universitas PGRI Palembang, 2023)
This study aims to determine eastern aesthetics in the traditional theater of Kemidi Rudat Lombok. The problem is focused on eastern aesthetic values ​​in Kemidi Rudat traditional theatrical performances as one of the arts that expresses aesthetic values ​​originating from cultural nobility. In order to address this problem, references to Soetarno's theory are used in a book on thoughts on eastern aesthetics which are more oriented to spirituality/spirits and moods. The data were collected through observation, interviews and documentation. This study uses a qualitative-descriptive approach using the semiotic analysis method of Tedeusz Kowzan theater. In summary and clearly this study shows that the eastern aesthetic values ​​of the Komidi Rudat theater include: 1) stoicism which is a reflection of the nature of human character which has the principle of maturity in thinking and acting, 2) adigang-adigung which is the antithesis of haughty nature and arrogance that should not be carried in humans. 3) item-putek which is the nature of human optimism in defending the truth and goodness (pute/white) and against bad and evil (item/black). 4) jiwe seli which is the nature of human concern in doing everything, that every work and problem can be solved together/cooperation. 5) sect which is human nature that has knowledge and a clear mind, and 6) manut which is human nature that obeys orders and rules. Keywords: Eastern Aesthetics, Traditional Theatre, Kimidi Rudat.